Impact of short-term housing temperature alteration on metabolic parameters and adipose tissue in female mice - Paz, Henry A.; Shashank, C. G.; Buddha, Lasya; Lam, Tian; Zhang, Taylor; Zhong, Ying; Sikes, James D.; Porter, Craig; Landes, Reid D.; Morello, Roy; Wankhade, Umesh D. (Frontiers in Endocrinology, 2025)
IntroductionAmbient temperature significantly influences physiological and metabolic processes in rodents, affecting obesity and related disorders. Mice housed below thermoneutral temperatures exhibit increased energy expenditure and sympathetic-driven brown fat activation, whereas thermoneutral housing (~30°C) reduces these responses. This study aimed to determine whether short-term exposure to altered housing temperatures before and during pregnancy induces lasting changes in maternal adipose tissue. We hypothesized that even brief exposure during this critical window could cause persistent structural and molecular alterations in adipose tissue.MethodsFemale C57BL/6J mice were housed at cold (CE, 8°C), thermoneutral (TN, 30°C), or standard room temperature (RT, 22°C) conditions for one week before and throughout pregnancy. All mice were returned to RT post-delivery. Phenotypic assessments—including glucose tolerance, energy expenditure, histology, and proteomics—were performed after lactation.ResultsTemperature exposure did not significantly affect litter size or pup survival. CE-exposed mice showed increased total body weight driven by lean mass gains and reduced fat mass. Adipose tissue showed smaller adipocytes in iWAT and increased vascularity in BAT, though no persistent changes in thermogenic gene expression or glucose homeostasis were observed. Proteomic analysis of iWAT identified 38 differentially expressed proteins, with enrichment of pathways related to mitochondrial function and mTOR signaling.DiscussionShort-term cold exposure induced lasting histological and proteomic changes in iWAT and BAT without sustained effects on energy metabolism, likely due to reversion to RT and limited sample size.ConclusionBrief temperature manipulation around pregnancy can durably alter maternal adipose tissue architecture and molecular signatures, underscoring ambient temperature as an important modulator of maternal metabolic adaptation.